All the Stars and Teeth - Book 1 - Grace, Adalyn (New York : Imprint, 2020)
"As princess of the island kingdom Visidia, Amora Montara has spent her entire life training to be High Animancer-- the master of souls. The rest of the realm can choose their magic, but for Amora, its never been a choice. To secure her place as heir to the throne, she must prove her mastery of the monarchys dangerous soul magic. When her demonstration goes awry, Amora is forced to flee. She strikes a deal with Bastian, a mysterious pirate: hell help her prove shes fit to rule, if shell help him reclaim his stolen magic. But sailing the kingdom holds more wonder--and more peril--than Amora anticipated. A destructive new magic is on the rise, and if Amora is to conquer it, shell need to face legendary monsters, cross paths with vengeful mermaids, and deal with a stowaway she never expected...or risk the fate of Visidia and lose the crown forever"--Provided by publisher.
Keywords: Princesses -- Juvenile fiction; Revenge -- Juvenile fiction; Magic -- Juvenile fiction; Islands -- Juvenile fiction; Sailing -- Juvenile fiction; Pirates -- Juvenile fiction; Mermaids -- Juvenile fiction; Princesses -- Fiction; Revenge -- Fiction; Magic -- Fiction; Islands -- Fiction; Sailing -- Fiction; Pirates -- Fiction; Mermaids -- Fiction; Princesses -- Fiction; Revenge -- Fiction; Magic -- Fiction; Islands -- Fiction; Sailing -- Fiction; Pirates -- Fiction; Mermaids -- Fiction; Kings, queens, rulers, etc. -- Fiction; Fantasy fiction